Prostate Specific Antigen Nadir After Radical Cystoprostatectomy in Patients With Benign Prostatic Tissue: A Benchmark To Define Biochemical Recurrence after Radical Prostatectomy - Hosseini, Seyed Yousef; Alemi, Mohsen; Amini, Erfan; Riazi, Naser (Urology Journal, 2019)
Purpose: Biochemical failure after radical prostatectomy has been defined based on retrospective studies in men who underwent RP for localized prostate cancer. Nevertheless, retrospective strategy and possibility of extra-prostatic extension overshadowed the accurateness of the aforementioned cut-off value. To define a more precise PSA nadir value, we estimated serum PSA after cystoprostatectomy in cases with bladder urothelial cancer and no evidence of prostate cancer. Materials and Methods: Study population consists of 52 subsequent patients who underwent radical cystoprostatectomy for muscle-invasive bladder cancer between December 2010 and December 2013. Patients with prostate adenocarcinoma and/or high grade prostate intraepithelial neoplasia were excluded from enrollment. Other exclusion criteria were prostate involvement with urothelial carcinoma, neoadjuvant or adjuvant chemotherapy and radiation therapy. Between all cases, 41 were enrolled for study. Serum PSA level was measured using immunochemiluminescence method among 6 months to 3 years after operation in study participants. Results: Forty-one patients with mean age of 66.4 ± 8.9 were assessed in this study. Average serum PSA level after radical cysto-prostatectomy was .037 ± .031 ng/mL (from .002 to .1). Serum PSA level was not impressed with type of diversion or interval between operation and PSA measurement. Average serum PSA level in this study was meaningfully lesser than .2 ng/mL which is contemplated as PSA nadir value after RP. Conclusion: Serum PSA level of 0.2 ng/mL as the definition for biochemical recurrence after RP may delay salvage treatment. Our results showed that cut off value of ?0.1 ng/mL may be more precise in the era of early salvage treatment.